2019
DOI: 10.1080/00343404.2019.1648786
|View full text |Cite
|
Sign up to set email alerts
|

Is there an optimal size for local governments? A spatial panel data model approach

Abstract: The paper presents a framework for determining the optimal size of local jurisdictions. To that aim, we first develop a theoretical model of cost efficiency that takes into account spatial interactions and spillover effects among neighbouring jurisdictions. The model solution leads to a Spatial Durbin panel data specification of local spending as a non-linear function of population size. The model is tested using local data over the 2003-2011 period for two aggregate (total and current) and four disaggregate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
1
7
0
1
Order By: Relevance
“…The study found economies of scale for some costs for land and existing facilities, but for most cost categories, the study found either no effect or diseconomies. These findings are consistent with the literature, which has generally shown either little or no evidence of economies of scale or evidence of diseconomies for cities above a threshold size [15,17,[28][29][30][31][32][33]. Results are also consistent with previous studies showing the effect is different for different spending categories [33,34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study found economies of scale for some costs for land and existing facilities, but for most cost categories, the study found either no effect or diseconomies. These findings are consistent with the literature, which has generally shown either little or no evidence of economies of scale or evidence of diseconomies for cities above a threshold size [15,17,[28][29][30][31][32][33]. Results are also consistent with previous studies showing the effect is different for different spending categories [33,34].…”
Section: Discussionsupporting
confidence: 92%
“…The evidence is mixed, however, and many studies find that either economies of scale do not exist or that economies of scale exist up to a point, and if population grows past that point, per capita spending rises, resulting in a U-shaped cost function [15,[28][29][30]. For example, research of Spanish municipalities found that economies of scale can be realized until the population reaches a critical size of about 10,800 [28], and a study of French communes found similar results but with a critical size of just 400, though the paper noted that about half of French communes have a population below this level [29]. Research in Queensland, Australia, found economies of scale up to about 99,000, with larger cities experiencing diseconomies [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The evidence from this plot enriches the considerations outlined in the previous discussion of the results (where we look at the distribution of the estimated municipal service levels and the distribution of the efficiency scores). The overall picture only weakly supports evidence for the presence of an optimal size in the adequate use of the financial resources around 10,000-15,000 citizens (also found for example in Italy by Agasisti andPorcelli, 2019 andin Spain by Hortas-Rico andRios, 2019). It strongly points at the presence of diseconomies of scale, especially for municipalities with more than 50,000 residents.…”
Section: Non-parametric Analysis Of Municipal Sizementioning
confidence: 84%
“…The journal is a pluralist forum, which showcases diverse perspectives and analytical techniques. Many papers published in the journal draw on leading quantitative research, including social network analysis (Derudder & Taylor, 2018;Martinus & Sigler, 2018), agent-based modelling (Pyka, Kudic, & Müller, 2019;Sebestyén & Varga, 2019), spatial econometrics (Ezcurra & Rios, 2019;Hortas-Rico & Rios, 2019), and panel data estimations (Cantner et al, 2019;Castellacci et al, 2019). Furthermore, novel methods from data science and big data analytics increasingly offer new opportunities as well as challenges, both theoretical and empirical, that may help answer complex questions and ask new ones within regional and subregional research.…”
Section: Looking Ahead: Regional Studies In the 2020smentioning
confidence: 99%